Germination effects on the physicochemical properties and sensory profiles of velvet bean (Mucuna pruriens) and soybean tempe - Astawan, Made; Prayudani, Ayu Putri Gitanjali; Haekal, Muhammad; Wresdiyati, Tutik; Sardjono, Ratnaningsih Eko (Frontiers in Nutrition, 2024)
Introduction Previous studies have shown that the velvet bean, an indigenous legume in Indonesia, possesses high protein content and bioactive compounds. However, the utilization of velvet beans in tempe production remains underexplored. Methods This study aims to address this research gap by investigating the physicochemical properties and sensory profiles of tempe made from velvet beans, both individually and in combination with soybean. The study involved the production of tempe using germinated and non-germinated velvet bean, soybean, and a soy-velvet bean combination (61:39% ratio). Physicochemical analyses, including hardness, firmness, colour, antioxidant capacity, proximate, pH, and titratable acidity, were conducted. Hedonic rating and Check-All-That-Apply (CATA) tests were also performed to assess the sensory attributes of fresh and fried tempe. Results and discussion Germination treatment of velvet bean resulted in tempe with reduced hardness, firmness, antioxidant capacity, and pH levels compared to non-germinated velvet bean tempe. However, velvet bean tempe exhibited a darker colour, higher antioxidant capacity, higher pH levels, and lower titratable acidity compared to soybean tempe and soy-velvet bean combination tempe. The protein content in velvet bean tempe was found to be below the required threshold of 15%. Hedonic rating tests revealed that fresh and fried velvet bean tempe received lower scores than other samples. CATA tests identified specific sensory attributes essential for fresh and fried tempe, including beany aroma, white colour, nutty aroma, golden brown colour, solid and crunchy texture, umami taste, and nutty aftertaste. These findings provide valuable insights into the potential applications of velvet beans in tempe production and emphasize the significance of considering germination as a factor affecting the quality and sensory attributes of tempe.